Guest editorial: industrial districts: towards the future (2022)
The notion of Industrial District (ID) was introduced by Alfred Marshall in the Principles of Economics (1890) and reintroduced a hundred years later by Giacomo Becattini (1979) in the main body of scientific literature. Since the 1990s, the notion of the Marshallian Industrial District (MID) has diffused rapidly in the scientific economic literature in English. What is extraordinary, however, is the variety and dynamism of the topics that the literature of the ID has produced over the past 40 years. When Giacomo Becattini published the seminal article “Dal settore industriale al distretto industriale. Alcune considerazioni sull’unità d’indagine dell’economia industriale” (the English version can be found in Becattini, 2004), in 1979, articles referring to ID were very scarce and came mainly from English economic historians analyzing IDs. From that moment on, the ID acquired its own entity, and a wide variety of topics on IDs began to be discussed; in the 1980s, typically those such as understanding sectors vs districts, local organization of production, the role of small firms, entrepreneurship, labor markets, technical change, among many more.